2008
DOI: 10.1073/pnas.0707265105
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial deafness alleles confer misreading of the genetic code

Abstract: Despite the fact that important genetic diseases are caused by mutant mitochondrial ribosomes, the molecular mechanisms by which such ribosomes result in a clinical phenotype remain largely unknown. The absence of experimental models for mitochondrial diseases has also prevented the rational search for therapeutic interventions. Here, we report on the construction of bacterial hybrid ribosomes that contain various versions of the mitochondrial decoding region of ribosomal RNA. We show that the pathogenic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 36 publications
5
123
0
2
Order By: Relevance
“…In previous study, it has been reported that AGs have a high affinity for ribosomal RNA and permeability transition in mitochondria, resulting in apoptosis via the inhibition of mitochondrial transcription or exaggerated oxidative stress, which are consistent with the molecular mechanisms for the ototoxicity and nephrotoxicity induced by AGs [24][25][26] . AGs have been clinically available as antibiotics for many years, and, unfortunately, can exert some irreversible adverse-effects, especially in the patients with a mitochondrial disease.…”
Section: Discussionsupporting
confidence: 52%
“…In previous study, it has been reported that AGs have a high affinity for ribosomal RNA and permeability transition in mitochondria, resulting in apoptosis via the inhibition of mitochondrial transcription or exaggerated oxidative stress, which are consistent with the molecular mechanisms for the ototoxicity and nephrotoxicity induced by AGs [24][25][26] . AGs have been clinically available as antibiotics for many years, and, unfortunately, can exert some irreversible adverse-effects, especially in the patients with a mitochondrial disease.…”
Section: Discussionsupporting
confidence: 52%
“…At the structural level, helix 44 interacts with helix 27. By modeling, nucleotide alterations in the lower stem of H44 have been suggested to affect this interaction and the relative movement between these two helices as part of the conformational change required in decoding (30). Apparently, the nature of the lower stem plays an important role in both spontaneous and drug-aggravated miscoding and determines the translational accuracy of the mutant decoding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Ribosomes were purified from bacterial cell pellets as described previously (30). In brief, ribosome particles were isolated by successive centrifugations and fractionated by sucrose gradient (10 -40%) centrifugation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For human mitochondrial H44 (hmt44) and E. coli H44 constructs, a hyperstable RNA tetraloop was inserted between the two strands (36 -39). The hmt44 construct corresponds to nucleosides 1483-1500 and 1549 -1569 of human mitochondrial 12S rRNA connected by a UUCG tetraloop (40). The E. coli H44 construct corresponds to nucleosides 1400 -1412 and 1488 -1502 of E. coli 16S rRNA (36) connected by the tetraloop GCAA.…”
Section: Methodsmentioning
confidence: 99%